MILENIAL INTERESTS ON ISLAMIC INSURANCE: THE ROLE OF MOBILE SERVICE AND SATISFACTION - Leviana Belianti; Fathimah Awliyaul Alim; Hizrina Awaliyah (Universitas Airlangga, 2019)
This research aims to predict millennial interest in using sharia insurance product mobile services in terms of usability dimensions (Safe, Convenient, Practical) and attractiveness (Visual, Price, Product) dimensions to interest in sharia insurance products through satisfaction mediation. This research observes 212 millennial respondents aged 20-37 years. By utilizing the SEM-PLS method, this research examines the feasibility of models and hypotheses. Estimation results reveal that millennials are interested in Islamic insurance mobile services based on the quality of practical and convenient mobile services, which has a positive value on satisfaction and interest in using Islamic insurance product mobile services. Thus, this research succeeded in renewing the view of the interests of insurance millennials. This research suggests the importance of the Islamic insurance industry in developing strategies designed to engage millennial customers with better service and increase their confidence in Islamic insurance mobile services.